2001
DOI: 10.1073/pnas.241333598
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the epsilon isoform of protein kinase C in the mammalian nerve terminal

Abstract: Activation of protein kinase C (PKC) by phorbol ester facilitates hormonal secretion and transmitter release, and phorbol esterinduced synaptic potentiation (PESP) is a model for presynaptic facilitation. A variety of PKC isoforms are expressed in the central nervous system, but the isoform involved in the PESP has not been identified. To address this question, we have applied immunocytochemical and electrophysiological techniques to the calyx of Held synapse in the medial nucleus of the trapezoid body (MNTB) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
1
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 45 publications
3
47
1
1
Order By: Relevance
“…As increased phosphorylation of S279 reflects an increase in the amount of PKCe that can be fully activated by lipid second messengers (Saitoh et al, 2001;Bayer et al, 2003;Zhou et al, 2003;Olive et al, 2005), these results suggest that ethanol stimulates a signaling cascade that increases the pool size of fully phosphorylated PKCe in the cerebellum. Although ethanol-stimulated PKCe phosphorylation at S729 in wildtype mice, we were only able to measure this increase 60 min following ethanol injection and not at 30 min or earlier time points.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…As increased phosphorylation of S279 reflects an increase in the amount of PKCe that can be fully activated by lipid second messengers (Saitoh et al, 2001;Bayer et al, 2003;Zhou et al, 2003;Olive et al, 2005), these results suggest that ethanol stimulates a signaling cascade that increases the pool size of fully phosphorylated PKCe in the cerebellum. Although ethanol-stimulated PKCe phosphorylation at S729 in wildtype mice, we were only able to measure this increase 60 min following ethanol injection and not at 30 min or earlier time points.…”
Section: Discussionmentioning
confidence: 80%
“…Phosphorylation at S729 permits full activity of PKCe when the enzyme is stimulated by lipid second messengers (Parekh et al, 1999;Takahashi et al, 2000). Thus, PKCe phosphorylation at S729 has been used as a marker for activation and posttranslational processing of the immature pool of PKCe that is not yet fully phosphorylated (Saitoh et al, 2001;Bayer et al, 2003;Zhou et al, 2003;Olive et al, 2005). Therefore, we used a phospho-specific antibody that detects phosphorylation of PKCe at S729 to investigate the regulation of the immature PKCe pool by ethanol.…”
Section: Ethanol Treatment Increases Pkce S729 Phosphorylation In Thementioning
confidence: 99%
“…It has been reported that actin filaments are abundant, intermixed with synaptic vesicles (10), and are present along the presynaptic membrane at the calyx of Held (11). Depolymerization of actin filaments suppresses the recovery of releasable SVs after depletion (12).…”
Section: Recovery Of Rapidly Releasing Vesicles After a Predepletingmentioning
confidence: 99%
“…Modulatory effects on quantal release can be examined in isolation while the terminal is voltage clamped and presynaptic membrane currents are monitored. Phalloidin staining showed that F-actin is confined to the distal end of the presynaptic terminal of the calyx of Held (Saitoh et al, 2001).…”
Section: Nem and Staurosporine Do Not Affect Recruitment Of Releasablmentioning
confidence: 99%
“…It is therefore unlikely that the effect of ATP-␥S is caused by activation of protein kinases. Phorbol esters, activators of protein kinase C, seem ineffective in modulating the recovery from vesicle pool depletion at the calyx synapse , although activation of PKC and the actin cytoskeleton are somehow related (Saitoh et al, 2001). …”
Section: Roles Of Nsf and Protein Kinases In Vesicle Recruitmentmentioning
confidence: 99%